Zur Karte des Kathmandu-Tals - Haffner, Willibald (ERDKUNDE, 1979)
Anyone studying the map of the Katmandu Valley is struck by the almost plastic contrast between the valley bottom, resulting from the gradual filling-up of a Pleistocene lake, and its mountainous, wooded frame dissected by U shaped valleys. A naturally favourable situation, together with a position that controls the pass of one of the most important trade and pilgrimage routes in the central Himalayas provided decisive impulses for the development of the three largest towns of Nepal: Katmandu, Patan and Bhaktapur. More than half of the 600,000 inhabitants of the Katmandu Valley, however, lives in smaller rural settlements and has made the irrigated valley bottom become the agriculturally most intensively utilised area. The field and place-names reflect the position of the Katmandu Valley as an area of penetration of Tibeto-Burmese and Indo-Aryan languages and indicate its complex underlying ethnic structure. The extensive temple districts of Pasupatinath, Swayambhunath and Bauddha are symbols of the unbroken religious traditions in Nepal. The rapid opening up to traffic of Nepal in general and the Katmandu Valley in particular constitute an example of change from a once closed Himalayan state that was hostile to strangers to a self-confident developing country with an active foreign policy and a tourist objective of the first order.